Refining Web-Based Job Search through Goal-Directed Design Improvement - Buana, I Gusti Agung Ayu Made Bidari Bening; Oetama, Raymond (The Indonesian Journal of Computer Science, 2023)
This study aims to improve a job search web application that not only addressed usability problems but also surpassed user expectations. A recently released job search web application was found to have usability problems during interviews with the Information Technology division. To measure the usability of the application and provide recommendations for improvement, the study uses the Goal-Directed Design framework, Performance Measurement method, and System Usability Scale measurement method. The evaluation was conducted twice, with the first assessment identifying problems and the second evaluation measuring the effectiveness of the recommendations made. The website prototype was developed and passed all test scenarios with an A+ grade. The modifications make important level of effectiveness, achieving an A+ grade with an 85% effectiveness rate. Furthermore, the website received exceptional user satisfaction, with an A+ rating and a score of 85.5 in usability satisfaction.